BRANDING AND BRAND MANAGEMENT IN INTERNATIONAL BUSINESS - Stošić Mihajlović, Ljiljana; Trajković, Svetlana (Journal of process management and new technologies, 2020)
Marketing is a scientific discipline oriented to practice, and is of particular importance for the functioning of business systems and organizations in the market economy, especially in modern secure business conditions and conditions of market globalization, strong competition in all business spheres, which is one of the main characteristics for the market in the Republic. Serbia.Creating, or creating and successfully developing a brand that can be equally involved with the world's leading brands in the fight for consumers, both in the domestic market and in other markets, becomes a major factor and key to the success of modern business and contemporary organizations of the world of work. Therefore, the aim of this paper is to point out the importance of brand management, through related units to guide in the specifics of brand building with an overview of relevant and present current concepts and examples, to bring closer to various aspects of brand management, with a special focus on the situation in Serbia and in our the immediate environment.
Keywords: brand management; branding; international business